Flash etching liquid medicine and preparation method and flash etching method thereof
By using flash etching potions with sulfuric acid/chloride system, combined with the synergistic effects of divalent copper ions, chloride ions, inorganic acids, pterin derivatives and multi-arm polyethylene glycol derivatives, the problem of unstable side etching potions during the etching process is solved, and a stable etching rate and good line binding force are achieved.
Patent Information
- Application Number
- CN202411796105.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-09
AI Technical Summary
During the etching process, the existing flash etching potions lead to unstable side corrosion during the difference in the etching rate of bottom copper and electroplated copper, which affects the binding force of the substrate and the copper layer, and is sensitive to changes in the concentration of chloride ions and hydrogen peroxide.
The flash corrosion potion using a sulfuric acid/chloride system contains divalent copper ions, chloride ions, inorganic acids, pterin derivatives and multi-arm polyethylene glycol derivatives. Through the synergistic action of these components, a stable etching rate and small undercut side etching is achieved.
The stability and etching effect of flash corrosion potion are achieved, ensuring good bonding between the lines and the substrate, and avoiding excessive side corrosion, improving the stability of the production process.
Smart Images

Figure CN119875643A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging substrate production, and in particular to a flash etching solution and a preparation method thereof and a flash etching method. Background Art
[0002] Semi-Additive Process (SAP) is a key technology in the field of integrated circuit (IC) substrate manufacturing. The method involves the following steps: first, a layer of base copper is deposited on the substrate as a seed layer for subsequent electroplating; then, the desired pattern is formed through processes such as dry film lamination, exposure, and development; then, electroplating is performed to increase the circuit thickness; finally, the base copper between the circuits is removed through a flash etching process to form a fine graphic circuit.
[0003] In the process of removing the bottom copper by flash etching, the flash etching solution will simultaneously etch the electroplated copper that forms the circuit and the bottom copper that serves as the bottom seed layer. Due to the differences in the preparation process of the bottom copper and the electroplated copper, such as the grain size, crystal form and density, the flash etching solution has different etching rates on them. This difference may cause excessive undercut at the junction of the bottom copper and the electroplated copper, which in turn affects the bonding strength between the substrate and the copper layer, causing problems such as flying wires and circuit breaks. Therefore, the etching rate stability and side etching control of the flash etching solution are key indicators to measure its performance.
[0004] At present, the flash etching solutions on the market are mainly based on the sulfuric acid / hydrogen peroxide system, which reduces the bottom side corrosion by adding revetments (side corrosion inhibitors). These revetments are usually small molecule compounds containing atoms such as N, O, and P. They are adsorbed on the copper surface through lone pairs of electrons, and with appropriate spray pressure, they can effectively reduce undercut. However, flash etching solutions in the sulfuric acid / hydrogen peroxide system have some disadvantages: they are sensitive to changes in chloride ion and hydrogen peroxide concentration, resulting in unstable etching rates and poor stability during continuous production; under the catalytic action of metal ions, the revetments will be oxidized by hydrogen peroxide, thus affecting their protective effect.
[0005] In contrast, the acidic copper chloride etching solution used in the traditional subtractive method is not interfered by chloride ions, but its etching rate is too fast (over 10μm / min) and is not suitable for etching bottom copper (less than 3μm) in the flash etching process. In addition, the acidic copper chloride etching solution contains strong oxidants such as sodium chlorate, which causes the side corrosion inhibitor to be oxidized quickly after addition, reducing its effect. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a flash etching solution of sulfuric acid / chloride system, which is not interfered by external chloride ions, has a stable etching rate and is simple to control on site.
[0007] The technical solution of the present invention is:
[0008] The invention provides a flash etchant comprising 15-25 g / l of divalent copper ions, 105-140 g / l of chloride ions, 100 g / L-180 g / L of inorganic acid, 0.02-0.1 g / l of pterin derivatives, 3 g / L-10 g / L of multi-arm polyethylene glycol derivatives and water.
[0009] Furthermore, the divalent copper ions come from at least one of copper chloride, copper sulfate and copper formate.
[0010] Furthermore, the chloride ions come from at least one of sodium chloride, potassium chloride and copper chloride or its hydrochloride.
[0011] Furthermore, the pterin derivative is at least one of 6-biopterin, 7,8-dihydrobiopterin, and pterin-6-carboxylic acid.
[0012] Furthermore, the multi-arm polyethylene glycol derivative is at least one of multi-arm polyethylene glycol amine, multi-arm polyethylene glycol maleimide, and multi-arm polyethylene glycol thiol.
[0013] Furthermore, the multi-arm polyethylene glycol amine is one of 4-arm polyethylene glycol amine, 6-arm polyethylene glycol amine and 8-arm polyethylene glycol amine.
[0014] Furthermore, the molecular weight of the 6-arm polyethylene glycol amine is 2K to 10K.
[0015] Furthermore, the concentration of the 6-arm polyethylene glycol amine is 3 g / L to 10 g / L.
[0016] The present invention further provides a method for preparing a flash etchant, which is used to prepare the above-mentioned flash etchant, comprising the following steps: dissolving divalent copper ions, chloride ions, inorganic acids, pterin derivatives, and multi-arm polyethylene glycol derivatives in water in proportion to form an aqueous solution, and stirring evenly to form a flash etchant.
[0017] The present invention further provides a flash etching method using a flash etching solution, wherein the flash etching solution is used to flash etch an integrated circuit substrate, wherein the spraying pressure is 1.2 to 1.8 kg / cm 2 , 10. The etching temperature is 25°C ~ 35°C, and the etching time is 90 ~ 150s.
[0018] The beneficial technical effects of the present invention are:
[0019] The flash etching solution of the present invention uses a sulfuric acid / chloride system. Compared with the sulfuric acid / hydrogen peroxide system solution, the solution contains a large amount of chloride ions and is not affected by a small amount of external chloride ions. Compared with the traditional acid chloride etching solution, the oxygen in the air is used as the recycling and regeneration oxidant of divalent copper, the lateral corrosion inhibitor will not be oxidized, and the solution has good stability. Through the synergistic effect of each component, a good etching effect can be obtained, which can effectively remove the bottom copper by flash etching, and at the same time, the undercut lateral corrosion is small, ensuring the bonding force between the circuit and the substrate. A small amount of pterin derivatives can form a corrosion cell effect of a small anode and a large cathode on the copper surface, promoting the etching of the bottom copper. A polymer compound multi-arm polyethylene glycol derivative is used as a lateral corrosion inhibitor, and the lateral corrosion at the bottom of the circuit after etching is small, and the linear shape is well maintained. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Example 1;
[0021] Figure 2 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Example 2;
[0022] Figure 3 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Example 3;
[0023] Figure 4 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Example 4;
[0024] Figure 5 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Example 5;
[0025] Figure 6 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Example 6;
[0026] Figure 7 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Example 7;
[0027] Figure 8 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Example 8;
[0028] Fig. 9 is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Comparative Example 3;
[0029] Fig.10 This is a metallographic section micrograph of an integrated circuit substrate after flash etching using the flash etching solution of Comparative Example 4. DETAILED DESCRIPTION
[0030] In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples. The following examples are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0031] The invention discloses a flash etching solution, which is applied to integrated circuit carriers. The flash etching solution comprises 15-25 g / l of divalent copper ions, 105-140 g / l of chloride ions, 100 g / l-180 g / l of inorganic acid, 0.02-0.1 g / l of pterin derivatives, 3 g / l-10 g / l of multi-arm polyethylene glycol derivatives and water. The flash etching solution of the invention uses a sulfuric acid / chloride system. Compared with a sulfuric acid / hydrogen peroxide system solution, the solution contains a large amount of chloride ions and is not affected by a small amount of external chloride ions. Compared with traditional acid chloride etching solutions, the use of oxygen in the air as a recycling oxidant for divalent copper will not oxidize the lateral corrosion inhibitor, and the solution has good stability. Through the synergistic effect of each component, a good etching effect can be obtained, which can effectively remove the bottom copper by flash etching, and at the same time, the undercut lateral corrosion is small, ensuring the bonding force between the circuit and the substrate. A small amount of pterin derivatives can form a corrosion cell effect of a small anode and a large cathode on the copper surface to promote the etching of the bottom copper. A polymer compound multi-arm polyethylene glycol derivative is used as a side erosion inhibitor, so that the side erosion at the bottom of the circuit after etching is small and the line shape is well maintained.
[0032] Furthermore, the divalent cupric ions in the flash etching solution come from at least one of cupric chloride, cupric sulfate, and cupric formate. Copper chloride, cupric sulfate, or cupric formate can provide divalent cupric ions after being dissolved in water. The divalent cupric ions react with copper as an oxidant to form monovalent cupric ions, which are then oxidized to divalent cupric ions by oxygen in the air, thereby achieving cyclic regeneration, a stable etching rate, and simple on-site control. Compared with traditional acidic chloride etching solutions, the flash etching solution of the present invention utilizes oxygen in the air as a cyclic regeneration oxidant for divalent copper, does not oxidize the side corrosion inhibitor, and has good stability.
[0033] Preferably, the divalent copper ions come from copper chloride, and the concentration of divalent copper ions provided by copper chloride is 15 g / L to 25 g / L.
[0034] Furthermore, the chloride ions are from at least one of sodium chloride, potassium chloride and copper chloride or its hydrochloride. Dissolving sodium chloride, potassium chloride or copper chloride or its hydrochloride in water can provide chloride ions. Chloride ions and cuprous chloride form soluble chlorides, which promote the copper etching reaction. Since the flash etching solution of the present invention uses a sulfuric acid / chloride system, compared with the sulfuric acid / hydrogen peroxide system solution, the flash etching solution contains a large amount of chloride ions and is not affected by a small amount of external chloride ions.
[0035] Preferably, the chloride ions come from sodium chloride, and the concentration of the chloride ions provided is 105 g / L to 140 g / L.
[0036] Preferably, the inorganic acid is sulfuric acid with a concentration of 100 g / L to 180 g / L. The inorganic acid provides an acidic environment, which is conducive to the dissolution of copper.
[0037] Furthermore, the pterin derivative is at least one of 6-biopterin, 7,8-dihydrobiopterin, and pterin-6-carboxylic acid. A small amount of pterin derivative can form a corrosion cell effect of a small anode and a large cathode on the copper surface, thereby promoting the etching of the bottom copper.
[0038] Preferably, the pterin derivative is pterin-6-carboxylic acid.
[0039] Furthermore, the concentration of the pterin derivative is 0.02 to 0.1 g / l, preferably 0.04 to 0.06 g / l.
[0040] Furthermore, the multi-arm polyethylene glycol derivative is a polymer compound. By using the polymer compound as a lateral corrosion inhibitor, the lateral corrosion at the bottom of the circuit after etching is small and the line shape is well maintained.
[0041] Furthermore, the multi-arm polyethylene glycol derivative is at least one of multi-arm polyethylene glycol amine, multi-arm polyethylene glycol maleimide, and multi-arm polyethylene glycol thiol.
[0042] Preferably, the multi-arm polyethylene glycol derivative is a multi-arm polyethylene glycol amine. By using multi-arm polyethylene glycol amine as a lateral corrosion inhibitor, there are multiple structures such as N, O atoms on its molecule that can provide lone pairs of electrons, and it has multiple potential active adsorption centers, which can be adsorbed on the metal surface more firmly. At the same time, the star-shaped branched structure of the multi-arm polyethylene glycol amine can not only ensure the contact area when adsorbed with the copper surface, but also can be combined with the copper surface to the greatest extent through the flexibility of its molecular structure to form a dense protective film. Through the synergistic effect of each component, the bottom copper can be quickly etched to form a circuit, and the formation of bottom lateral corrosion can be effectively avoided. In addition, the multi-arm polyethylene glycol amine can be adsorbed on the copper surface to form an isolation film. With the appropriate spray pressure, the flash etching solution can break through the isolation film on the front of the circuit, but for the isolation films on both sides of the circuit, they are maintained due to insufficient pressure, thereby achieving the purpose of reducing lateral corrosion.
[0043] Furthermore, the multi-arm polyethylene glycol amine is one of 4-arm polyethylene glycol amine, 6-arm polyethylene glycol amine and 8-arm polyethylene glycol amine.
[0044] Furthermore, the molecular weight of the 6-arm polyethylene glycol amine is 2K to 10K, preferably 4K.
[0045] Furthermore, the concentration of the 6-arm polyethylene glycol amine is 3 g / L to 10 g / L, preferably 4 g / L to 6 g / L.
[0046] The present invention further provides a method for preparing a flash etchant, which is used to prepare the above-mentioned flash etchant, comprising the following steps: dissolving divalent copper ions, chloride ions, inorganic acids, pterin derivatives, and multi-arm polyethylene glycol derivatives in water in proportion to form an aqueous solution, and stirring evenly to form a flash etchant.
[0047] The present invention further provides a flash etching method using a flash etching solution, wherein the flash etching solution is used to flash etch an integrated circuit substrate, wherein the spraying pressure is 1.2 to 1.8 kg / cm 2 , 10. The etching temperature is 25°C ~ 35°C, and the etching time is 90 ~ 150s.
[0048] In order to clearly illustrate the flash etch solution and its preparation method and the flash etch method of the present invention, the following description part is described in detail with specific examples and comparative examples.
[0049] Embodiment 1:
[0050] The divalent copper ions come from copper sulfate and the concentration is 20g / l.
[0051] Chloride ions come from sodium chloride at a concentration of 120 g / l.
[0052] The inorganic acid is sulfuric acid with a concentration of 150g / / L.
[0053] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.05 g / l.
[0054] The multi-arm polyethylene glycol derivative is a 6-arm polyethylene glycol amine with a molecular weight of 4K and a concentration of 5 g / L.
[0055] The above components are dissolved in water according to proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0056] Embodiment 2:
[0057] The divalent copper ions come from copper sulfate and the concentration is 15g / l.
[0058] Chloride ions come from sodium chloride at a concentration of 105 g / l.
[0059] The inorganic acid is sulfuric acid with a concentration of 100g / / L.
[0060] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.02 g / l.
[0061] The multi-arm polyethylene glycol derivative is a 6-arm polyethylene glycol amine with a molecular weight of 4K and a concentration of 3 g / L. The above components are dissolved in water according to a proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0062] Embodiment 3:
[0063] The divalent copper ions come from copper chloride and the concentration is 25g / l.
[0064] Chloride ions come from sodium chloride and copper chloride, with a concentration of 140g / l.
[0065] The inorganic acid is sulfuric acid with a concentration of 180g / / L.
[0066] The pterin derivative was pterin-6-carboxylic acid at a concentration of 1 g / l.
[0067] The multi-arm polyethylene glycol derivative is a 6-arm polyethylene glycol amine with a molecular weight of 2K, and the concentration is 10 g / L. The above components are dissolved in water according to the proportion to form an aqueous solution, and the flash etchant is formed after being stirred evenly.
[0068] Embodiment 4:
[0069] The divalent copper ions come from copper formate and the concentration is 20g / l.
[0070] Chloride ions come from sodium chloride at a concentration of 120 g / l.
[0071] The inorganic acid is sulfuric acid with a concentration of 150g / / L.
[0072] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.05 g / l.
[0073] The multi-arm polyethylene glycol derivative is a 6-arm polyethylene glycol amine with a molecular weight of 10K and a concentration of 3 g / L. The above components are dissolved in water according to a proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0074] Embodiment 5:
[0075] The divalent copper ions come from copper chloride and the concentration is 20g / l.
[0076] Chloride ions come from potassium chloride at a concentration of 120 g / l.
[0077] The inorganic acid is sulfuric acid with a concentration of 150g / / L.
[0078] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.05 g / l.
[0079] The multi-arm polyethylene glycol derivative is a 4-arm polyethylene glycol amine with a molecular weight of 10K and a concentration of 5 g / L. The above components are dissolved in water according to a proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0080] Embodiment 6:
[0081] The divalent copper ions come from copper chloride and the concentration is 25g / l.
[0082] Chloride ions come from sodium chloride and copper chloride, with a concentration of 120g / l.
[0083] The inorganic acid is sulfuric acid with a concentration of 120g / / L.
[0084] The pterin derivative was 6-biopterin at a concentration of 0.1 g / l.
[0085] The multi-arm polyethylene glycol derivative is an 8-arm polyethylene glycol amine with a molecular weight of 2K and a concentration of 3 g / L.
[0086] The above components are dissolved in water according to proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0087] Embodiment 7:
[0088] The divalent copper ions come from copper sulfate and the concentration is 15g / l.
[0089] Chloride ions come from sodium chloride and potassium chloride at a concentration of 100 g / l.
[0090] The inorganic acid is sulfuric acid with a concentration of 100g / / L.
[0091] The pterin derivative was 7,8-dihydrobiopterin at a concentration of 0.02 g / l.
[0092] The multi-arm polyethylene glycol derivative is a multi-arm polyethylene glycol maleimide with a molecular weight of 2K and a concentration of 3 g / L.
[0093] The above components are dissolved in water according to proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0094] Embodiment 8:
[0095] The divalent copper ions come from copper formate and the concentration is 20g / l.
[0096] Chloride ions come from sodium chloride at a concentration of 120 g / l.
[0097] The inorganic acid is sulfuric acid with a concentration of 150g / / L.
[0098] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.05 g / l.
[0099] The multi-arm polyethylene glycol derivative is a multi-arm polyethylene glycol thiol with a molecular weight of 4K and a concentration of 5 g / L.
[0100] The above components are dissolved in water according to proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0101] Comparative Example 1:
[0102] The divalent copper ions come from copper sulfate and the concentration is 20g / l.
[0103] Chloride ions come from sodium chloride at a concentration of 120 g / l.
[0104] The inorganic acid is sulfuric acid with a concentration of 150g / / L.
[0105] The above components are dissolved in water according to proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0106] Comparative Example 2:
[0107] The divalent copper ions come from copper sulfate and the concentration is 20g / l.
[0108] Chloride ions come from sodium chloride at a concentration of 120 g / l.
[0109] The inorganic acid is sulfuric acid with a concentration of 150g / / L.
[0110] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.01 g / l.
[0111] The multi-arm polyethylene glycol derivative is a 6-arm polyethylene glycol amine with a molecular weight of 4K and a concentration of 5 g / L.
[0112] The above components are dissolved in water according to proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0113] Comparative Example 3:
[0114] The divalent copper ions come from copper sulfate and the concentration is 20g / l.
[0115] Chloride ions come from sodium chloride at a concentration of 120 g / l.
[0116] The inorganic acid is sulfuric acid with a concentration of 150g / / L.
[0117] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.2 g / l.
[0118] The multi-arm polyethylene glycol derivative is a 6-arm polyethylene glycol amine with a molecular weight of 4K and a concentration of 5 g / L.
[0119] The above components are dissolved in water according to proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0120] Comparative Example 4:
[0121] The divalent copper ions come from copper sulfate and the concentration is 15g / l.
[0122] Chloride ions come from sodium chloride at a concentration of 105 g / l.
[0123] The inorganic acid is sulfuric acid with a concentration of 100g / / L.
[0124] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.02 g / l.
[0125] The multi-arm polyethylene glycol derivative is a 6-arm polyethylene glycol amine with a molecular weight of 4K and a concentration of 0.5 g / L. The above components are dissolved in water according to a proportion to form an aqueous solution, and stirred evenly to form a flash etchant.
[0126] Comparative Example 5:
[0127] The divalent copper ions come from copper sulfate and the concentration is 15g / l.
[0128] Chloride ions come from sodium chloride at a concentration of 105 g / l.
[0129] The inorganic acid is sulfuric acid with a concentration of 100g / / L.
[0130] The pterin derivative was pterin-6-carboxylic acid, and the concentration was 0.02 g / l.
[0131] The multi-arm polyethylene glycol derivative is a 6-arm polyethylene glycol amine with a molecular weight of 4K and a concentration of 15 g / L. The above components are dissolved in water according to a proportion to form an aqueous solution, and stirred evenly to form a flash etchant. Further, the performance of the flash etchants of the above examples and comparative examples is tested.
[0132] Test board: The base copper is H series copper foil from Mitsui, Rz = 3μm. Production board process flow: film pasting - exposure - development - pattern electroplating - film stripping - washing and drying, ready for use.
[0133] Spraying equipment: Etching test tank, the nozzle is 5cm away from the board surface, the nozzle is fan-shaped, and during the etching process, the board surface automatically swings back and forth to ensure uniformity.
[0134] Test process: Fix the test board in the etching test tank, start the swing etching and start the timing, and take it out in time after the time is up, wash and blow dry. The spray pressure is 1.5±0.1kg / cm2, the etching temperature is 30±2℃, and the etching time is 120±30s.
[0135] Determination of performance indicators:
[0136] Circuit appearance: If there is no residual copper on the substrate between the circuits, it is qualified; if there is residual copper, it is unqualified.
[0137] Circuit undercut: Slice and fill the test piece with glue after clean etching without residual copper, and observe and measure the circuit undercut amount under a microscope after polishing. The undercut amount on one side is less than 1μm, which is qualified.
[0138] The performance test results of the flash erosion potions of the above examples and comparative examples are shown in Tables 1 and Figures 1 to 10 shown.
[0139] Table 1 Performance results of various embodiments and comparative examples
[0140] Example / Comparative Example Line appearance Metallographic section Left side erosion μm Right side erosion μm Example 1 No residual copper, qualified Figure 1 0.4466 0.4094 Example 2 No residual copper, qualified Figure 2 0.2977 0.521 Example 3 No residual copper, qualified Figure 3 0.3683 0.2947 Example 4 No residual copper, qualified Figure 4 0.5955 0.4466 Example 5 No residual copper, qualified Figure 5 0.7815 0.6327 Example 6 No residual copper, qualified Figure 6 0.6327 0 Example 7 No residual copper, qualified Figure 7 0.8188 0.3722 Example 8 No residual copper, qualified Figure 8 0.6327 0.2977 Comparative Example 1 There is residual copper, unqualified / / / Comparative Example 2 There is residual copper, unqualified / / / Comparative Example 3 No residual copper, qualified Fig. 9 1.079 1.154 Comparative Example 4 No residual copper, qualified Fig.10 1.489 0.6699 Comparative Example 5 There is residual copper, unqualified / / /
[0141] It can be seen from Examples 1 to 8 that after the flash etching experiment using the flash etching solution of the present invention, the bottom copper on the circuit substrate after copper skin etching is etched cleanly without any residual copper, and the circuit appearance is qualified. In addition, the single-side undercut side etching amount is less than 1μm, and the side etching amount is qualified.
[0142] By comparing Example 1 and Comparative Example 1, it can be seen that the flash etching solution of Comparative Example 1 does not contain pterin derivatives and multi-arm polyethylene glycol derivatives. Therefore, bottom copper remains on the substrate between the circuits in Comparative Example 1, and the circuit appearance is unqualified. This indicates that when sulfuric acid chloride etching solution is used directly, the bottom copper between the circuits will not be etched cleanly.
[0143] By comparing Example 1 and Comparative Example 2, it can be seen that the amount of pterin derivatives used in Comparative Example 2 is reduced. Therefore, base copper remains on the substrate between the circuits in Comparative Example 2, and the circuit appearance is unqualified. This indicates that when the pterin derivatives are insufficiently used, etching will not be complete.
[0144] By comparing Example 1 and Comparative Example 3, it can be seen that the amount of pterin derivatives is increased in Comparative Example 3. Therefore, there is no residual bottom copper on the substrate between the circuits in Comparative Example 3, and the circuit appearance is qualified. However, the side etching amount on the left and the side etching amount on the right are both greater than 1 μm, the side etching amount is large, and it is unqualified. This shows that when the amount of pterin derivatives is excessive, the etching is too fast and the side etching is large.
[0145] By comparing Example 2 and Comparative Example 4, it can be seen that the amount of multi-arm polyethylene glycol derivatives used in Comparative Example 4 is reduced. Therefore, there is no residual bottom copper on the circuit substrate in Comparative Example 4, and the circuit appearance is qualified. However, the side etching amount on the left and the side etching amount on the right are both greater than 1 μm, the side etching amount is large, and it is unqualified. It shows that when the amount of multi-arm polyethylene glycol derivatives used is reduced, the protective effect decreases and the side etching is large.
[0146] By comparing Example 2 and Comparative Example 5, it can be seen that the amount of the multi-arm polyethylene glycol derivative was increased in Comparative Example 4. Therefore, in Comparative Example 2, base copper remained on the substrate between the circuits, and the circuit appearance was unqualified. This indicates that when the amount of the multi-arm polyethylene glycol derivative used was too large, the base copper was not etched cleanly.
[0147] In summary, the present invention provides a flash etching solution, a preparation method thereof, and a flash etching method. The flash etching solution uses a sulfuric acid / chloride system. Compared with a sulfuric acid / hydrogen peroxide system solution, the solution contains a large amount of chloride ions and is not affected by a small amount of external chloride ions. Compared with the traditional acid chloride etching solution, the oxygen in the air is used as a recycling oxidant for divalent copper, the lateral corrosion inhibitor will not be oxidized, and the solution has good stability. Through the synergistic effect of each component, a good etching effect can be obtained, which can effectively remove the bottom copper by flash etching, and at the same time, the undercut lateral corrosion is small, ensuring the bonding force between the circuit and the substrate. A small amount of pterin derivatives can form a corrosion cell effect of a small anode and a large cathode on the copper surface, promoting the etching of the bottom copper. A polymer compound multi-arm polyethylene glycol derivative is used as a lateral corrosion inhibitor, and the lateral corrosion at the bottom of the circuit after etching is small, and the linear shape is well maintained.
[0148] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the technical principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A flash erosion potion, characterized in that: The invention comprises 15-25 g / l of divalent copper ions, 105-140 g / l of chloride ions, 100 g / L-180 g / L of inorganic acid, 0.02-0.1 g / l of pterin derivatives, 3 g / L-10 g / L of multi-arm polyethylene glycol derivatives and water.
2. The flash erosion solution according to claim 1, characterized in that: The divalent copper ions are from at least one of copper chloride, copper sulfate and copper formate.
3. The flash erosion solution according to claim 1, characterized in that: The chloride ions come from at least one of sodium chloride, potassium chloride and copper chloride or its hydrochloride.
4. The flash erosion solution according to claim 1, characterized in that: The pterin derivative is at least one of 6-biopterin, 7,8-dihydrobiopterin, and pterin-6-carboxylic acid.
5. The flash erosion solution according to claim 1, characterized in that: The multi-arm polyethylene glycol derivative is at least one of multi-arm polyethylene glycol amine, multi-arm polyethylene glycol maleimide and multi-arm polyethylene glycol thiol.
6. The flash erosion solution according to claim 5, characterized in that: The multi-arm polyethylene glycol amine is one of 4-arm polyethylene glycol amine, 6-arm polyethylene glycol amine and 8-arm polyethylene glycol amine.
7. The flash erosion solution according to claim 6, characterized in that: The molecular weight of the 6-arm polyethylene glycol amine is 2K to 10K.
8. The flash erosion solution according to claim 6, characterized in that: The concentration of the 6-arm polyethylene glycol amine is 3 g / L to 10 g / L.
9. A method for preparing a flash erosion solution, characterized in that: The method for preparing the flash etching solution as claimed in any one of claims 1 to 8 comprises the following steps: dissolving divalent copper ions, chloride ions, inorganic acids, pterin derivatives, and multi-arm polyethylene glycol derivatives in water in proportion to form an aqueous solution, and stirring evenly to form the flash etching solution.
10. A flash etch method using a flash etch solution, characterized in that: The integrated circuit substrate is flash-etched using the flash-etching solution as claimed in any one of claims 1 to 8, wherein the spraying pressure is 1.2 to 1.8 kg / cm 2 , 10. The etching temperature is 25℃~35℃, and the etching time is 90~150s.
Citation Information
Patent Citations
Aqueous clean solution with low copper etch rate for organic residue removal improvement
CN104395989A
Chemical etching method for obtaining high-transmittance aluminum alloy
CN109055937A
Etching composition and application thereof
CN117089842A
Etching liquid
JP1998251876A
Etching liquid for copper or copper alloy, and method for producing electronic substrate using the same
JP2004256901A